A method for an approximate numerical solution of two-point boundary value problems: nonstandard finite difference method on a semi-open interval. (6th June 2023) - Pandey, Pramod Kumar
In this paper, a nonstandard finite difference technique is considered with semi-uniform nodes for the numerical solution of the two-point boundary value problem subject to Dirichlet boundary conditions in the semi-open domain. To overcome the discretisation issue at the right open end of the domain, i.e., at infinity-semi-uniform nodes were used. The boundary condition at infinity is taken into account precisely by the so-generated semi uniform nodes. The numerical experiment with a proposed method carried out by considering model problems, including singular problems. The method proposed in the paper produces a decent approximate solution of the considered problems and totally conquers the issue of boundary conditions at infinity and singularity.